Exploring school staff members’ understanding about influences on the experiences and belonging of students of Caribbean Descent in schools: A Reflexive Thematic Analysis. - Dyer, Lydia (2022)
The current research utilised reflexive Thematic Analysis (Braun & Clarke, 2022) to explore the shared understanding of school staff members regarding the experiences and sense of belonging of students of Caribbean descent in school and the influences over these. The barriers within the English education system for students, who identify as having Caribbean heritage and a ‘black’ racialised identity, are widely acknowledged in the research and literature across time (e.g., Coard, 1971, Demie & McLean 2017a, Wallace & Joseph Salisbury, 2021). The narratives of young people in the research support this and emphasise the importance of a sense of belonging to the school experience. School staff are indicated as being influential to both the experience and sense of belonging for students. As professionals within the school system, with considerable influence, it was deemed important to gather their understanding and perceptions on how the school context may be shaping young people’s experiences to support transformation.